Clinical standardized fMRI reveals altered language lateralization in brain tumor patients - Partovi, Sasan; Rapps, Nora; Rengier, Fabian; Stippich, Christoph (American journal of neuroradiology, 2012)
BACKGROUND AND PURPOSE: Brain tumors affecting language-relevant areas may influence language lateralization. The purpose of this study was to systematically investigate language lateralization in brain tumor patients using clinical language fMRI, comparing the results with a group of healthy volunteers. MATERIALS AND METHODS: Fifty-seven strictly right-handed patients with left-hemispheric-space intracranial masses (mainly neoplastic) affecting either the Broca area (n = 19) or Wernicke area (n = 38) were prospectively enrolled in this study. Fourteen healthy volunteers served as a control group. Standardized clinical language fMRI, using visually triggered sentence- and word-generation paradigms, was performed on a 1.5T MR scanner. Semiautomated analyses of all functional data were conducted on an individual basis using BrainVoyager. A regional lateralization index was calculated for Broca and Wernicke areas separately versus their corresponding right-hemisphere homologs. RESULTS: In masses affecting the Broca area, a significant decrease in the lateralization index was found when performing word generation (P = .0017), whereas when applying sentence generation, the decrease did not reach statistical significance (P = .851). Masses affecting the Wernicke area induced a significant decrease of the lateralization index when performing sentence generation (P = .0007), whereas when applying word generation, the decrease was not statistically significant (P = .310). CONCLUSIONS: Clinical language fMRI was feasible for patients with brain tumors and provided relevant presurgical information by localizing essential language areas and determining language dominance. A significant effect of the brain masses on language lateralization was observed, with a shift toward the contralesional, nondominant hemisphere. This may reflect compensatory mechanisms of the brain to maintain communicative abilities.
Published online December 13, 2012
Gesehen am 25.06.2018